Sudden Withdrawal or Introduction of Drugs and their Clinical Consequences - Banday, Tanveer Hassan; Bashir, Sadaf (Journal of Medicine, 2015)
Abstract not available J MEDICINE July 2015; 16 (2) : 103-104